Metode Uploading sebagai Sarana Pertunjukan Musik Online: Studi Kasus Duo Guitar Dumotsiny - Amra Reza; DJ Dimas Phetorant; Demi Tatipikalawan (Institut Seni Indonesia Denpasar, 2022)
Purpose: Technology provides color and a new way of viewing music. Music performances that originally relied on physical and communal meeting rooms had to adapt to social distancing policies due to the pandemic. This condition attracted the attention of researchers to observe the dynamics of the lives of art workers in the field of music. Research methods: Researchers observe musical performances that are displayed on several digital media platforms. Many of the artists who use the uploading method. The research method used is qualitative using a case study approach with the subject of the guitar duo Dumotsiny. Results and discussion: As a result, online music performances can be done by uploading by recording audio and video separately or by recording audio and video simultaneously. Implication: In music, every era always experiences changes in technology.